2013
DOI: 10.5713/ajas.2012.12700
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Level Water-soluble Pentosans, Alkaline-extractable Pentosans, and Xylanase on the Growth and Development of Broiler Chicks

Abstract: This study investigated the effects of low levels of water-soluble pentosans (WSP), alkaline-extractable pentosans (AEP), and xylanase on the growth and organ development of broiler chicks. Three hundred and fifty 1-d-old female broiler chicks were randomly allocated into seven experimental groups of five pen replicates, with ten chicks per replicate. The control group consumed a corn-soybean meal-based diet. Six dietary treatment groups consumed the basal diet supplemented with one of the following: WSP at 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Changes in pH may be due to modification of the intestinal microflora as a result of enzyme supplementation. Sheng et al (2013) found that the addition of xylanase reduced ileal pH in broiler chickens. They measured Lactobacillus concentrations in rectal digesta which was increased with the addition of xylanase suggesting the lower pH level was due to increased microflora proliferation and fermentation.…”
Section: Discussionmentioning
confidence: 98%
“…Changes in pH may be due to modification of the intestinal microflora as a result of enzyme supplementation. Sheng et al (2013) found that the addition of xylanase reduced ileal pH in broiler chickens. They measured Lactobacillus concentrations in rectal digesta which was increased with the addition of xylanase suggesting the lower pH level was due to increased microflora proliferation and fermentation.…”
Section: Discussionmentioning
confidence: 98%
“…It measures the indigestible cellulose, pentosans, lignin, and other components. However, fiber is well known to reduce risk of diabetes, cardiovascular disease, and blood cholesterol [ 36 , 37 ]. TDF was analyzed in all the different PS fractions of the APF and CPF.…”
Section: Resultsmentioning
confidence: 99%